2004
DOI: 10.1097/01.ju.0000105073.67242.eb
|View full text |Cite
|
Sign up to set email alerts
|

Dietary L-Arginine Supplementation Improves the Glomerular Filtration Rate and Renal Blood Flow After 24 Hours of Unilateral Ureteral Obstruction in Rats

Abstract: This study demonstrates that L-arginine supplementation can improve renal function in acute UUO. This finding suggests that NO system may be a future site of pharmacological intervention for UUO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
30
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 17 publications
3
30
1
Order By: Relevance
“…apoptotic cells when HKC-8 cells were subjected to pressure of 60 mmHg for 18 h (Fig. 2C) (6,18,29). The earliest increase in iNOS expression was documented at 10 min following UUO (15).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…apoptotic cells when HKC-8 cells were subjected to pressure of 60 mmHg for 18 h (Fig. 2C) (6,18,29). The earliest increase in iNOS expression was documented at 10 min following UUO (15).…”
Section: Resultsmentioning
confidence: 99%
“…Increasing NO metabolites has been shown to be protective in UUO (18). The irreversible inhibitor 1400W significantly increased HKC-8 cell death at 30 and 60 min [3 Ϯ 0.01 vs. 12 Ϯ 0.03% (P Ͻ 0.05, 30 min), 9 Ϯ 0.01 vs. 16 Ϯ 0.01% (P Ͻ 0.05, 60 min); Fig.…”
Section: Effect Of Nf-b Inhibition On Inos Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reduced levels of L-arginine have been observed in renal failure, but the clinical relevance is uncertain, as the measured serum concentrations are well in excess of the K m for eNOS (1,38). Nevertheless, both clinical (20,47,52,60) and experimental studies (12,14,18,22,23,36,44) have demonstrated that substrate supplementation stimulates NO production and attenuates renal damage and salt-sensitive hypertension. Furthermore, chronic NO inhibition with N G -nitro-Larginine methyl ester (L-NAME), an antagonist for L-arginine, causes salt-sensitive hypertension and the development of renal injury (62).…”
mentioning
confidence: 99%